2013
DOI: 10.5935/1676-4285.20133791
|View full text |Cite
|
Sign up to set email alerts
|

The role of a nurse in the management of medical-hospital material: an integrative review

Abstract: The object of the study is the management of medical-hospital supplies. This is an area that requires the nurse to have specific knowledge and which has currently sparked discussions among experts on the subject. Aim: To characterize the production of knowledge on the management of medical-hospital material conducted by nurses. Method: A retrospective, descriptive method that followed the steps of an integrative review. For the research the Lilacs, Medline and Google scholardatabases were used. Results: We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…As an integrative review reported that the management of material resources is still incipient in the national scenario of the nursing practice, nurses need to gain specific knowledge (11) . A research carried out in six teaching hospitals indicates changes in the participation of nurses in planning, purchasing, storaging, distributing and controlling materials.…”
Section: Discussionmentioning
confidence: 99%
“…As an integrative review reported that the management of material resources is still incipient in the national scenario of the nursing practice, nurses need to gain specific knowledge (11) . A research carried out in six teaching hospitals indicates changes in the participation of nurses in planning, purchasing, storaging, distributing and controlling materials.…”
Section: Discussionmentioning
confidence: 99%
“…This surgical planning will be responsible for predicting, providing, and maintaining the necessary resources for the intraoperative period. 1 Material resource (MR) planning is linked to nursing and care provided to the patients. A study pointed out the lack of MR and equipment as the main barrier in the care process according to 87.5% of nurses interviewed.…”
Section: Original Articlementioning
confidence: 99%
“…The control procedure to ensure the availability of these resources is based on quality, amount, time, and cost. 1 In hospital institutions, it is common to observe that insufficiency, lack, or low quality of the materials used create delays or cancellations of surgeries, thus increasing the stress in the whole multiprofessional team. There are, therefore, interruptions in the care provided or barriers in care planning.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation